2015
DOI: 10.1155/2015/298430
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Labeling of Bone Marrow-Derived Rat Mesenchymal Stem Cells: Their Use in Differentiation and Tracking

Abstract: Mesenchymal stem cells (MSCs) are promising candidates for cellular therapies due to their ability to migrate to damaged tissue without inducing immune reaction. Many techniques have been developed to trace MSCs and their differentiation efficacy; however, all of these methods have limitations. Conjugated polymer based water-dispersible nanoparticles (CPN) represent a new class of probes because they offer high brightness, improved photostability, high fluorescent quantum yield, and noncytotoxicity comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
(45 reference statements)
0
11
0
1
Order By: Relevance
“…Then the culture medium was changed every three days. After two passages, cells were used in the whole study [39]. …”
Section: Methodsmentioning
confidence: 99%
“…Then the culture medium was changed every three days. After two passages, cells were used in the whole study [39]. …”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the labeled mesenchymal stem cells (MSCs) migrated to the liver and retained their labels in an in vivo liver regeneration model. These studies demonstrated that the utilization of florescence labeling could be a promising tool for the tracking of stem cells transplanted in liver to understand differentiation and homing mechanisms [28]. Wang et al investigated upconversion nanoparticles- (UCNPs-) labeled mouse MSCs intravenous transplanted into mice and imaged using an in vivo upconversion luminescence (UCL) imaging system, observing the translocation of MSCs from lung where they initially accumulated, to liver [29].…”
Section: Imaging Methods To Monitor Transplanted Stem Cells In Animentioning
confidence: 99%
“…LRP-1 enables transcytosis of ligands across the BBB, and drugs that exploit this receptor, GRN1005 and ANG1005, have been well-tolerated in HGG and effective in crossing of the BBB and are currently being studied in recurrent GBM [129].…”
Section: Other Delivery Methodsmentioning
confidence: 99%